Diseño e implementación de un sistema de monitoreo que permita evaluar la eficiencia energética e hidráulica del Hospital Regional Isidro Ayora. - Cuenca Tinitana Julio César (2006)
This job develops the design and execution about the monitoring system for evaluates energetic-hydraulic efficiency in Hospital Isidro Ayora, by means of LabVIEW software. At First, it does a complete description about the energetic and hydraulic installations inside the institution, in which detail the most important elements of each one, structure and their principal fails, especially that refers about consumption measurement. After that, we refer about SCADA systems, their constitutive elements, main station, communication systems, RTUs and other field devices, and principal characteristics and functions. This part also presents many proposals about the measurement system structure, starting from the basic variants with instruments based on 4-20mA, to modern systems with field bus communication. Finally, presents a system based on LabVIEW 7.1 software. It details how the analog measurements are done through the USB 6008 data acquisition device. Their own LabVIEW VIs used in data acquisition are described and also the specific developed application like flow measurement, water volume, electric power and energy, handling and saving data, files and report generation, those which integrated inside an application have competition to SCADA. The work was carried out under the direction of the Engineer Francisco Aleaga, the Doctor's Orlys Torres and of the M. Sc. Wilbert Acuña consultantship and the collaboration of the Department of Maintenance of the Regional Hospital Isidro Ayora of Loja.